Bacteria that cause infections of the lower respiratory tract in patients in the intensive care unit (ICU) - Pattanaik, Mitrabinda; Dash, Ansuman; Mishra, Madhushree; Satpathy, Sonam (South Eastern European Journal of Public Health, 2025)
Worldwide, intensive care units (ICU) deal with a significant number of lower respiratory tract infections (LRTIs). Critical care unit patients are at increased risk for contracting multidrug-resistant infections, such as Pseudomonas aeruginosa, Klebsiella pneumoniae, Acinetobacter baumannii, and methicillin-resistant Staphylococcus aureus (MRSA). Their susceptibility is heightened because they have compromised immune systems, must undergo invasive medical procedures, and spend more time in the hospital. The aim of the present study was to determine the bacteria that cause infections of the lower respiratory tract in patients admitted in the intensive care unit (ICU). Approach and Materials: The research was placed in Rourkela's Hi-Tech Medical College & Hospital from January to June of 2024. Out of 150 people who agreed to take part in the study, participants were ICU patients whose physicians had reason to assume they had a lower respiratory tract infection. Adults and infants alike contributed clinical samples of sputum and tube secretions for the study. A diagnosis of LRTI was made for patients who were observed from the start of the study until they were sent home. Some of the symptoms included a high temperature, clear ET secretions, infiltrates seen on chest X-ray, an increase in white blood cell counts, and indicators of inflammation. The research determined that 150 patients from the PICU and MICU had their LRT samples evaluated. Results from culture tests showed a single pathogen in 82% of instances, and 62% of patients had positive results. In 89.77% of patients, it was determined that the sickness was caused by Gram-negative bacteria. Species of Acinetobacter, Staphylococcus aureus, Klebsiella, Pseudomonas, and Escherichia coli were the most prevalent. The resistance to Klebsiella and Acinetobacter species was higher in patients who were adults or older. The outcomes are: Rare LRTIs commonly cause antibiograms and culture isolation in patients in the critical care unit. Because of factors such as antibiotic overuse, treatment resistance, and neglect, health care-associated infections pose an issue in critical care units in India. The effective and prompt treatment of infections depends on the implementation of an antimicrobial stewardship policy.